Find the general solution of each differential equation, expressing y explicitly in terms of x.
3) dy/dx= 3x2(y+1)
4) dy/dx = y-1 / 2x-1
(i)
"\\frac{dy}{dx} = 3x\u00b2(y+1)"
=> "\\frac{dy}{y+1} = 3x\u00b2dx"
Integrating we get
"\\int\\frac{dy}{y+1} = \\int3x\u00b2dx"
=> ln |y+1| = x³ + ln |A| where ln |A| is integration constant
=> ln |y+1| - ln |A| = x³
=> "ln \\mid {\\frac {y+1}{A}}\\mid = x\u00b3"
=> y + 1 = Aex³
=> y = Aex³ - 1
This is the solution of the given differential equation
(ii)
"\\frac{dy}{dx} = \\frac{y-1}{2x-1}"
=> "\\frac{dy}{y-1} = \\frac{dx}{2x-1}"
Integrating we get
=> "\\int\\frac{dy}{y-1} =\\frac{1}{2}\\int \\frac{2dx}{2x-1}"
=> ln |y-1| = "\\frac{1}{2} ln |2x-1| + ln |A|"
where ln |A| is integration constant
=> ln |y-1| - ln |A| = "\\frac{1}{2} ln|2x-1|"
=> "ln \\mid\\frac{y-1}{A}\\mid= ln{\\sqrt{2x-1}}"
=> "\\frac{y-1}{A}= \\sqrt{2x-1}"
=> y - 1 = A"\\sqrt{2x-1}"
=> y = 1 + A"\\sqrt{2x-1}"
This is the solution of the given differential equation
Comments
Leave a comment